Problematika Dakwah Jama’ah Salafi di Tanjung Pauh Kecamatan Pangkalan Koto Baru Kabupaten Limapuluh Kota - Hayatun Nufus; Penmardianto Penmardianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Da'wah in its implementation encounters obstacles and da'wah problems. This research is motivated by the problematic da'wah faced by the salafi congregation in Tanjung Pauh, Pangkalan Koto Baru Subdistrict on the implementation of da'wah which is not going well. Backgrounded by the state and background of human resources both in terms of education and cultural background. There are still many people who have not fully implemented Islamic law and there are still many people who commit actions that deviate from Islamic teachings such as gambling, drinking alcohol, many people who have not and or neglect prayer, lack of social boundaries between young men and women, still lack of parents who teach their children about Islamic values in everyday life. The type of research used is field research with a descriptive qualitative approach. The data collection used is observation, interview, and documentation. The results of the research are the problematic da'wah of the salafi congregation in Tanjung Pauh, Pangkalan Koto Baru District, Limapuluh Kota Regency, which consists of the problematic maddah (da'wah material), namely from da'wah material that is less adapted to the background of the community. Second: problematic thariqah (method of da'wah), namely in terms of the method of da'wah al-mujadalah al-ahsan.